2014
DOI: 10.1371/journal.pone.0094225
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Systemic Inflammation and Multi Organ Damage after Global Ischemia/Reperfusion in the Arctic Ground Squirrel

Abstract: IntroductionCardiac arrest (CA) and hemorrhagic shock (HS) are two clinically relevant situations where the body undergoes global ischemia as blood pressure drops below the threshold necessary for adequate organ perfusion. Resistance to ischemia/reperfusion (I/R) injury is a characteristic of hibernating mammals. The present study sought to determine if arctic ground squirrels (AGS) are protected from systemic inflammation and multi organ damage after CA- or HS-induced global I/R and if, for HS, this protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
6
40
1
Order By: Relevance
“…How mammalian hibernators are able to adapt to rapidly fluctuating oxygen levels without incurring oxidative damage, and how they avoid reperfusion injury in the brain and other sensitive tissues, is not well understood. Multiple studies have shown that hibernators display resistance to ischemia/reperfusion injury and, during torpor, increase expression of molecules that help regulate oxidative stress, such as superoxide dismutase 1 and 2, catalase, and glutathione peroxidase (2,(43)(44)(45)(46). Interestingly, uncoupling proteins have been linked to reduction of reactive oxygen species formation (47).…”
Section: Discussionmentioning
confidence: 99%
“…How mammalian hibernators are able to adapt to rapidly fluctuating oxygen levels without incurring oxidative damage, and how they avoid reperfusion injury in the brain and other sensitive tissues, is not well understood. Multiple studies have shown that hibernators display resistance to ischemia/reperfusion injury and, during torpor, increase expression of molecules that help regulate oxidative stress, such as superoxide dismutase 1 and 2, catalase, and glutathione peroxidase (2,(43)(44)(45)(46). Interestingly, uncoupling proteins have been linked to reduction of reactive oxygen species formation (47).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, livers removed from summer ground squirrels and stored cold for up to 72 h retain viability and function better than rats, and this retention of performance actually improves in the hibernation season (178). Accordingly, cardiac arrest has virtually no effect on arctic ground squirrel liver, but causes considerable damage in rats (25). Because mammalian brain is inherently susceptible to interruptions of blood flow and O 2 supply, hibernator brains have been studied extensively.…”
Section: Are Hibernators Better At Withstanding Hypoxia/ischemia?mentioning
confidence: 99%
“…In rats, cardiac arrest damages a large proportion of CA1 hippocampal neurons, but virtually no damage is seen in euthermic arctic ground squirrels (74). Tissue ischemia resistance may also translate to higher levels of organization, as arctic ground squirrels survive extreme blood loss better than rats (25).…”
Section: Are Hibernators Better At Withstanding Hypoxia/ischemia?mentioning
confidence: 99%
“…Many animals such as birds and mammals drastically reduce energy expenditure during times of cold exposure, food shortage, or drought, by temporarily abandoning optimal body temperature by a process called torpor (seasonal torpor in case of hibernation, daily torpor at night). A state of torpor might represent a cold ischemia condition, which could be followed by reperfusion when temperature and metabolism are restored [76]. In this respect, necroptosis has been shown to contribute to damage induced by ischemia-reperfusion injury [77].…”
Section: Rhim-mediated Interactions Evolved To Activate Necroptosis Imentioning
confidence: 99%